Pengaruh Pelatihan Kerja Dan Keselamatan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan Pada PT Sanchem Industrial Pertiwi Di Balaraja Kabupaten Tangerang - Abdillah Fathah; Sam Cay (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of Job Training and Occupational Safety and Health (OSH) on Employee Performance at PT Sanchem Industrial Pertiwi in Balaraja, Tangerang Regency. The background of this research is based on the importance of improving the quality of human resources through job training and the implementation of occupational safety and health systems to support optimal employee performance. The research method used is a quantitative method with an associative approach. The population in this study consisted of all employees of PT Sanchem Industrial Pertiwi totaling 57 people, using a saturated sampling technique in which the entire population was used as respondents. Data collection techniques were carried out through questionnaires, observation, and documentation studies. Data analysis methods included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests with the assistance of SPSS software. The results showed that Job Training had a positive and significant effect on Employee Performance, as evidenced by the t-count value of 14.465 > t-table 2.004 and a significance value of < 0.05. Occupational Safety and Health (OSH) also had a positive and significant effect on Employee Performance with a t-count value of 15.916 > t-table 2.004 and a significance value of < 0.05. Simultaneously, Job Training and Occupational Safety and Health (OSH) had a positive and significant effect on Employee Performance with an F-count value of 128.443 > F-table 3.17 and a significance value of < 0.05.